Fatigue life prediction of 5083 and 5A06 aluminum alloy T-welded joints based on the fatigue characteristics domain - Li Zou; Xinhua Yang; Jianrong Tan; Hongji Xu; Yibo Sun (Fracture and Structural Integrity)
Three-point bending fatigue test of 5083 and 5A06 aluminum alloy T-welded joints is carried out, and the fatigue life of the specimens with different influencing factors are obtained. Finite element model of the T-welded joint is established and the nodal force based structural stress is calculated. Neighborhood rough set theory is used for analysis of the factors which influence the fatigue life of the aluminum alloy welded joints. Key influencing factors are studied and the fatigue characteristic domains are determined. The master S-N curve characterized by the nodal force based structural stress range and cycles to failure on semi log coordinate as well as S-N curves corresponding to the fatigue characteristic domain is fitted. A case study of fatigue life prediction of 5A06 aluminum alloy welded joint indicates the effectiveness of the fatigue life prediction method based on the fatigue characteristic domain.